PARA PELAKU MENCARI PENYEMBUHAN : Berteologi Dengan Narasi Para Pelaku Tragedi ’65 di Timor Barat - Mery Kolimon (Institut Filsafat dan Teknologi Kreatif Ledalero, 2015)
Half century after the anti-Communist Tragedy in Indonesia, including East Nusa Tenggara Province, one of the important questions need to be coped with is the impact of the Tragedy to the perpetrators. Some of those who took part in the arrest, persecution, and murder of the victims, are still alive. Because of the taboo of talking about the Tragedy and its impact among Indonesia society, they hide their feeling for nearly 50 years. They hold guilty/sin, shame, and hero feelings at the same time. Their narratives offer us rich theological themes and pastoral challenge. This paper tries to identify the theological themes arose in the narratives of some perpetrators.